Strengthening Ecological Fiqh Values in Building SDGs Madrasah Models Through Environmental Outdoor Education - Hidayah, Ulil; Tobroni; Faridi (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This study aims to strengthen the values of ecological fiqh in building a madrasa model that supports the achievement of Sustainable Development Goals (SDGs). Ecological fiqh, which is based on Islamic principles such as balance (mizan), non-destruction (la tufsidu fil ard), and sustainability (istidamah), offers a relevant conceptual framework to address global challenges related to the environment. Madrasas, as educational institutions based on Islamic values, have the potential to become centers of educational transformation in instilling ecological awareness and supporting the goals of the SDGs, especially quality education (SDG 4), environmental action (SDG 13) and life on land (SDG 15). This study uses a conceptual method with a theoretical analysis approach. Data and information were obtained through a literature review of various literatures, including primary sources in ecological fiqh and SDGs documents. The analysis was conducted to formulate the principles of ecological fiqh that can be integrated into the madrasa education model. The results of the study indicate that strategies for strengthening ecological values include integration into the curriculum, developing an environmentally friendly culture in madrasas, and involving the educational community and the wider community. This study provides a conceptual contribution in formulating an SDGs-based madrasah model based on ecological fiqh. Recommendations are provided for policy makers, madrasah managers, and related parties in building an educational ecosystem that supports global sustainability.